Emerging roles of protein modifications in sexual reproduction and pathogenesis of filamentous fungi - Li, Xiaoxing; Zhou, Xin; Luo, Yuchen; Xue, Luman; Tong, Xinxin; Guo, Jinlin (Frontiers in Microbiology, 2026)
Posttranslational modifications play pivotal roles in the regulation of protein function, enabling precise and dynamic control of diverse cellular processes in fungi. Classical and emerging PTMs, such as phosphorylation, ubiquitination, acetylation, lysine succinylation, and SUMOylation, glycosylation, lipidation modifications, S-acylation, or S-palmitoylation, critically modulate the activity and behavior of proteins. In recent years, research efforts have increasingly focused on global PTMs profiling and functional characterization across fungal species. PTMs function in multiple cellular processes, such as meiosis, cell wall integrity, autophagy, reactive oxygen species metabolism, RNA editing, finely regulating the fungal sexual development and virulence. More recently, the biomolecular condensates dynamics resembled by PTMs modulate host–pathogen interactions. Furthermore, the crosstalk between different PTMs on a single protein and interacting proteins allows for sophisticated regulatory control over fungal development, adaptation, and pathogenicity. However, the full scope of PTMs in the fungal sexual development and pathogenesis in plant remains to be fully elucidated. This review offers a comprehensive analysis of the roles of PTMs in sexual development of the model and plant pathogenic filamentous fungi. It offers mechanistic insights into how the PTMs regulate biological processes, cellular functions and integrate environmental cues, ultimately modulating sexual progression and virulence. A deeper understanding of the roles and regulatory mechanisms of PTMs will facilitate the development of effective strategies for industrially valuable fungi breeding and plant diseases control.